2004
DOI: 10.1016/s1054-139x(03)00269-6
|View full text |Cite
|
Sign up to set email alerts
|

Primary and secondary sexual abstinence in high school students

Abstract: Fear of adverse consequences and normative beliefs about the appropriateness of having sexual intercourse were most frequently endorsed as important reasons by both groups of abstainers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Studies of ''primary'' and ''secondary'' abstinence or being a ''reborn virgin'' identified what differentiates these groups. For instance, Loewenson, Ireland, and Resnick (2004) found that among males, ''secondary'' virgins were more likely to have caused a pregnancy.…”
Section: New Perspectives On Sexual Behaviorsmentioning
confidence: 99%
“…Studies of ''primary'' and ''secondary'' abstinence or being a ''reborn virgin'' identified what differentiates these groups. For instance, Loewenson, Ireland, and Resnick (2004) found that among males, ''secondary'' virgins were more likely to have caused a pregnancy.…”
Section: New Perspectives On Sexual Behaviorsmentioning
confidence: 99%
“…Those who responded "no" or "don't know" were skipped on questions on sexual behavior and classified here as primary abstainers. About 15-25% of [12][13][14] year olds in the four countries reported that they had never heard of sexual intercourse. reproductive health programs.…”
Section: Introductionmentioning
confidence: 99%
“…While there is much support for the promotion of sexual abstinence among the youth, there is a paucity of studies that examine characteristics of young people who choose to abstain from sexual intercourse. Thus, much less is known about the reasons why some adolescents decide to abstain from sexual intercourse than about factors that predispose the youth to risky sexual behaviors 13,14 . Nonetheless, young people may choose to delay sexual intercourse due to individual, socio-cultural, and other contextual factors that, if better understood, can substantially inform HIV, STI, and early pregnancy prevention messages 9 .…”
Section: Introductionmentioning
confidence: 99%
“…n Being determined to abstain from sex, perceiving greater benefits from abstinence, being older at sexual debut, and using a condom at sexual debut are protective. Intention to have sex and being ambivalent or motivated to have a child promote risk Goodenow et al;Loewenson, Ireland, & Resnick, 2004;Shafii, Stovel, Davis, & Holmes, 2004). Implications for NP practice:…”
Section: From a Teen Point Of View: Adolescent Perspectivesmentioning
confidence: 99%